New constraints on mid-Proterozoic ocean redox from stable thallium isotope systematics of black shales. (15th December 2021) - Li, Zijian; Cole, Devon B.; Newby, Sean M.; Owens, Jeremy D.; Kendall, Brian; Reinhard, Christopher T.
Abstract: Stable thallium (Tl) isotope data from organic-rich siliciclastic sedimentary rocks have the potential to track ocean redox state on a broad scale. Here, we report new Tl isotope data from the Mesoproterozoic Velkerri Formation (Roper Group) and the Paleoproterozoic Wollogorang Formation (Tawallah Group), McArthur Basin, Northern Territory, Australia, and interpret these in the context of rhenium-osmium (Re-Os) geochronometry on the same sample suite. Previous work has shown that marine black shales from the Velkerri Formation provide evidence for closed-system Re-Os systematics, yielding a precise isochron with an age of 1361 ± 21 Ma that agrees well with independent age constraints for the unit. The isotopic composition of authigenic Tl in euxinic black shales from the upper Velkerri Formation (ε 205 Tl = −2.4 ± 0.8, 2SD) indicates that the Tl isotope composition of local seawater at 1.36 Ga was within a plausible range for Tl inputs to the ocean. Isotope mass-balance modeling of the Tl isotope system within a Monte Carlo framework suggests that the Tl isotopic composition of seawater at 1.36 Ga was homogenous on a global scale and that the burial of Mn-oxides exerted minimal isotopic leverage on the Tl isotope composition of seawater at 1.36 Ga. Taken together with existing Mo, Cr, and U isotope data from the same samples, these observations are consistent with a low-O2 ocean-atmosphere system during this period of the Mesoproterozoic. Previous work has shown that the Re-Os systematics of black shales from the older (1.73 Ga) Wollogorang Formation are scattered and yield an erroneously young isochron age of 1359 ± 150 Ma, which has been attributed to post-depositional hydrothermal alteration at ∼1640 Ma. We observe no systematic relationship between stable Tl isotope compositions and the extent of alteration as gauged by open-system Re-Os behavior (−4.7 ± 1.4 for the upper Wollogorang Formation and −4.8 ± 0.4 for the lower Wollogorang Formation), in marked contrast to previous observations for the molybdenum (Mo) and uranium (U) isotope systems. The invariant signature of the Tl isotope data suggests the Tl isotope system was largely unperturbed during hydrothermal alteration. However, it remains difficult to definitively rule out the possibility that authigenic Tl isotope signatures have been overprinted by later localized hydrothermal fluid alteration in the Wollogorang Formation shales. These observations highlight the potential insights afforded by evaluating open-system behavior via radiogenic isotope systems together with other stable isotope tracers in efforts to reconstruct the redox landscape of Earth's oceans over time.